(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Rasipuram Krishna swami Narayan, one of the foundingpillars of Indian writing in English is an institution in himself. Born and brought up in a traditional SouthIndian family in 1906, Narayan is a true Indian both in spirit andthought. Much has been said aboutNarayan as an outstanding and unassailable story-teller.